2014
DOI: 10.3389/fpsyg.2014.00038
|View full text |Cite
|
Sign up to set email alerts
|

A dynamically minimalist cognitive explanation of musical preference: is familiarity everything?

Abstract: This paper examines the idea that attraction to music is generated at a cognitive level through the formation and activation of networks of interlinked “nodes.” Although the networks involved are vast, the basic mechanism for activating the links is relatively simple. Two comprehensive cognitive-behavioral models of musical engagement are examined with the aim of identifying the underlying cognitive mechanisms and processes involved in musical experience. A “dynamical minimalism” approach (after Nowak, 2004) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 82 publications
5
38
0
3
Order By: Relevance
“…One explanation is that the repeated pairings of framing vignettes would also improve cognitive fluency, in line with the predictions by Belke and colleagues (e.g., Belke et al, 2010). Alternatively, these results fit the dynamic minimalist account proposed by Schubert et al (2014b), which proposes that each of the cognitive factors that determine musical response also generate musical pleasure. In other words, any kind of mental representation associated with music can add to cognitive activation, which, they claim, generates pleasure.…”
Section: General Discussion and Conclusionsupporting
confidence: 79%
“…One explanation is that the repeated pairings of framing vignettes would also improve cognitive fluency, in line with the predictions by Belke and colleagues (e.g., Belke et al, 2010). Alternatively, these results fit the dynamic minimalist account proposed by Schubert et al (2014b), which proposes that each of the cognitive factors that determine musical response also generate musical pleasure. In other words, any kind of mental representation associated with music can add to cognitive activation, which, they claim, generates pleasure.…”
Section: General Discussion and Conclusionsupporting
confidence: 79%
“…This suggests that certain musical abilities (either innate or acquired through music education) may influence the transcriptional responses of listening to music. Previous works have shown that the familiarity of music attained through music education or repeated music exposure is known to largely influence the rewarding aspects of listening to music ( Sarkamo et al, 2008 ; Salimpoor et al, 2009 ; Van den Bosch, Salimpoor & Zatorre, 2013 ; Schubert, Hargreaves & North, 2014 ). Here, we acknowledge that the effect of music exposure on human gene expression could be very subjective and may vary depending on several factors such as age, sex, culture, previous listening habits, music education and training and personal liking of music, as recently discussed ( Wong et al, 2007 ; Salimpoor et al, 2009 ; Van den Bosch, Salimpoor & Zatorre, 2013 ; Mikutta et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…乐偏好具有重要关联 [50,68,69] . Martindale 和Moore [68] 较早探讨了音乐文化经验在音乐偏好产生过程中的 作用机制, 提出了音乐偏好的"原型"假设(prototype hypothesis).…”
Section: 已有研究总体上认为 音乐文化经验与个体音unclassified
“…Brattico等人 [66] 发现, 音乐文化经验不同的个体在边 缘系统部分具有不同的激活特点, 音乐专业者相比 具有更强的激活. Alluri等人 [80] 是 目 前 理 论还 难 以 做 出较 好 解 释 的问 题 [50] . 例 如 , 多项研究发现相比不和谐音程, 刚刚出生或半岁以 下的婴儿就能表现出对和谐音程的偏好 [81,82] , 这意 味着音乐偏好的发生仍然存在重要的生物学基础, 仍然具有不需要习得的过程 [67] .…”
Section: 近期 一些研究利用脑成像技术探讨了音乐文unclassified
See 1 more Smart Citation